ANALISIS PELAKSANAAN KEWAJIBAN ATAS PAJAK PENGHASILAN PASAL 21 PADA RUMAH SAKIT X DI KLATEN-JAWA TENGAH - Nila Nurma Ningsih; Diska Arliena Hafni (Review of Applied Accounting Research (RAAR), 2021)
The purpose of research is to analyze the implementation of the obligations of Hospital X in Klaten on income tax Article 21. This study employed a qualitative research method using a descriptive approach. There were used primary data and secondary data. The data were collected by through observation, interviews and documentation. The data analysis techniques used were descriptive analysis and comparative analysis. The results of this study indicated that during 2017 until 2019, Hospital X carried out its obligations for income tax article 21 quite well, although in some cases, there were still errors. Based on the activities of calculating and withholding Article 21 Income Tax, Hospital X was still not in accordance with the tax law. In contrast to the calculation and withholding of Article 21 Income Tax, the activities of depositing and reporting taxes at Hospital X during 2017 until 2019 had carried out their obligations on time and in accordance with existing rules or laws.